Tonoplast Aquaporins Facilitate Lateral Root Emergence. Issue 3 (22nd January 2016) - Reinhardt, Hagen; Hachez, Charles; Bienert, Manuela Désirée; Beebo, Azeez; Swarup, Kamal; Voß, Ute; Bouhidel, Karim; Frigerio, Lorenzo; Schjoerring, Jan K.; Bennett, Malcolm J.; Chaumont, Francois
Abstract : Aquaporins located in the vacuolar membrane contribute to the proper development of lateral roots. Abstract: Aquaporins (AQP s) are water channels allowing fast and passive diffusion of water across cell membranes. It was hypothesized that AQP s contribute to cell elongation processes by allowing water influx across the plasma membrane and the tonoplast to maintain adequate turgor pressure. Here, we report that, in Arabidopsis ( Arabidopsis thaliana ), the highly abundant tonoplast AQP isoforms AtTIP1;1, AtTIP1;2, and AtTIP2;1 facilitate the emergence of new lateral root primordia (LRPs ). The number of lateral roots was strongly reduced in the triple tip mutant, whereas the single, double, and triple tip mutants showed no or minor reduction in growth of the main root. This phenotype was due to the retardation of LRP emergence. Live cell imaging revealed that tight spatiotemporal control of TIP abundance in the tonoplast of the different LRP cells is pivotal to mediating this developmental process. While lateral root emergence is correlated to a reduction of AtTIP1;1 and AtTIP1;2 protein levels in LRPs, expression of AtTIP2;1 is specifically needed in a restricted cell population at the base, then later at the flanks, of developing LRPs . Interestingly, the LRP emergence phenotype of the triple tip mutants could be fully rescued by expressing AtTIP2;1 under its native promoter. We conclude that TIP isoforms allow the spatial and temporal fine-tuning of cellular water transport, which is critically required during the highly regulated process of LRP morphogenesis and emergence.